Pressure distribution in a squeeze film spherical bearing with rough surfaces lubricated by an Ellis fluid - Jurczak, Paweł; Falicki, Jarosław (Zielona Góra: Uniwersytet Zielonogórski)
In this paper, the solution to a problem of pressure distribution in a curvilinear squeeze film spherical bearing is considered. The equations of motion of an Ellis pseudo-plastic fluid are presented. Using Christensen`s stochastic model of rough surfaces, different forms of Reynolds equation for various types of surface roughness pattern are obtained.
Keywords: pseudo-plastic model of Ellis fluid; thrust curvilinear bearings; modified Reynolds equation